Co-cultivation of activated sludge and microalgae for the simultaneous enhancements of nitrogen-rich wastewater bioremediation and lipid production - Leong, W.-H. (Taiwan Institute of Chemical Engineers, 2018)
The symbiotic relationships between activated sludge and microalgae were explored for bio-remediating nitrogen-rich wastewater and producing lipid-based biofuel simultaneously. Various inoculation ratios of activated sludge to microalgae (AS:MA) biomasses were employed to unveil the mechanism of NH4 +-N removal in relation to lipid production from algal-bacterial biomass. The presence of nitrifiers in converting NH4 +-N into oxidized nitrogen (NO2 â-N and NO3 â-N) had greatly enhanced the total nitrogen removal in the co-cultivation bioreactors as compared with the individual culture of either activated sludge or microalgae. Accordingly, achieving near complete nitrogen removal (97â98) when the bioreactors were inoculated with AS:MA ratios of 1:0.75 and beyond. The kinetic growths of co-cultivated activated sludge and microalgae biomasses were also investigated using Verhulst model; demonstrating a significant increase of specific biomass growth rate with increasing of initial microalgae inoculation ratio. The AS:MA ratio of 1:0.75 was considered optimum for the symbiotic algal-bacterial interactions, attaining the highest lipid yield of 130 mg/L and flocculation efficiency of 42 which would aid the biomass harvesting process. Â© 2018 Taiwan Institute of Chemical Engineers